Semibatch operation and primary cyclization effects in homogeneous free-radical crosslinking copolymerizations - Dias, Rolando (2008)
A theoretical analysis is presented on the use of semibatch reactors for producing non-linear copolymers through the homogeneous free-radical polymerization of mono- and divinyl-monomers. The kinetic scheme distinguishes two kinds of pendant double bonds and five kinds of polymer radicals, as it also takes into account the primary cyclization of terminal divinyl units. In spite of the fairly large number of groups and reactions, the generating function of vector chain length distribution of polymer species can still be accurately computed by a numerical implementation of the method of characteristics and thus average molecular weights before and after gelation can be reliably obtained. The influence of feed policies of the monomers, initiator and transfer agent on gelation, average chain lengths and weight fraction of sol is discussed, as well as their sensitivity to some kinetic parameters.